An integrated network platform for contextual prioritization of drugs and pathways1. Issue 11 (13th November 2015) - Segura-Cabrera, Aldo; Singh, Navneet; Komurov, Kakajan
<x xml:space="preserve">Abstract</x> Network-based analyses facilitate contextual drug repositioning.